Visuo-Haptic Interactions in Unilateral Spatial Neglect: The Cross Modal Judd Illusion - Mancini, Flavia; Bricolo, Emanuela; Mattioli, Flavia C.; Vallar, Giuseppe (Frontiers in Psychology, 2011)
Unilateral spatial neglect has been mainly investigated in the visual modality; only a few studies compared spatial neglect in different sensory modalities, and explored their multisensory interactions, with controversial results. We investigated the integration between vision and haptics, through a bisection task of a crossmodal length illusion, the Judd variant of the Müller-Lyer illusion. We examined right-brain-damaged patients with (n=7) and without (n=7) left unilateral spatial neglect, and neurologically unimpaired participants (n=14) in the bisection of Judd stimuli under visual, haptic, and visuo-haptic presentation. Neglect patients showed the characteristic rightward bias in the bisection of a baseline stimulus in the visual modality, but not in the haptic and visuo-haptic conditions. The illusory effects were preserved in each group and in each modality, indicating that the processing of the length illusion is independent of the presence of deficits of spatial attention and representation. Spatial neglect can be modality-specific, but visual and tactile sensory inputs are properly integrated.